(Unused) potentials of educators' covert language policies at public schools in Limpopo, South Africa. Issue 3 (26th May 2020) - Kretzer, Michael M.; Kaschula, Russell H.
ABSTRACT: Language policy is an influencing factor of the educational outcome for pupils in Africa. Colonial languages have been largely used and African Languages are neglected. Despite this, the South African Constitution (1996) declares eleven official languages. However, curricular developments favour Afrikaans and English. To analyse the implementation of the official language policy, we focus on Limpopo Province. Over 1000 questionnaires were answered by teachers. This approach aimed to analyse the language practices and language attitudes of teachers. Schools in Limpopo showed significant differences between the official language policy and the daily language practices. Some teachers implement the official language policy; others use one or more African languages in their oral communications during the lessons in the form of Code Switching. This is seen in relation to the contemporary debates regarding translanguaging as an educational pedagogy.